Only the Destined (The Way of Steel-Book 3) - Morgan, Rice (Lukeman Literary, 2019)
"Morgan Rice did it again! Building a strong set of characters, the author delivers another magical world. ONLY THE WORTHY is filled with intrigue, betrayals, unexpected friendship and all the good ingredients that will make you savor every turn of the pages. Packed with action, you will read this book on the edge of your seat." --Books and Movie Reviews, Roberto Mattos From Morgan Rice, #1 Bestselling author of THE QUEST OF HEROES (a free download with over 1,000 five star reviews), comes a riveting new fantasy series. In ONLY THE DESTINED (The Way of Steel-Book Three), Royce, 17, must embark with his friends on an epic journey across the sea to find the magic relic that can lead him to his father. With the king gathering an army to attack their lands, the fate of his people depends on him. Genevieve, meanwhile, finally aware of the evil nature of her noble guests, must make an epic decision that will decide her own life or death. ONLY THE DESTINED weaves an epic tale of friends and lovers, of knights and honor, of betrayal, destiny and love. A tale of valor, it draws us into a fantasy world we will fall in love with, and appeals to all ages and genders. Book #4 in the series will be available soon.
Keywords: Sci-fi, fantasy; Dobrodružství, napětí, fantasy